Ratiometric upconversion nanothermometry with dual emission at the same wavelength decoded via a time-resolved technique - Xiaochen Qiu; Qianwen Zhou; Xingjun Zhu; Zugen Wu; Wei Feng; Fuyou Li (Nature Communications, 2020)
Traditional ratiometric temperature monitoring is challenging due to the variation in tissue absorption and scattering of different wavelengths. Here, the authors show improved accuracy by using emission at the same wavelength, but different luminescent lifetimes decoded by a time-resolved technique.